2023
DOI: 10.24018/ejgeo.2023.4.1.376
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Solar Electricity Generation from Floating Photovoltaics Installed in Water Dams in the Island of Crete, Greece

Abstract: The role of solar energy for heat and power generation is very important during the transition to a low carbon economy. Floating solar photovoltaics consists of a novel and rapidly growing sustainable energy technology having many advantages compared to conventional ground-mounted solar photovoltaic systems. Aim of the current research is the investigation of the possibility of installing floating photovoltaics in the existing water reservoirs in the island of Crete, Greece. Data on existing water dams in Cret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…They proposed the delay of the energy transition for some years for a better preparation of the national plan. Vourdoubas [31] has estimated the solar electricity generation from FPVs in water reservoirs in Greece. The author estimated that the nominal power of the FPVs that can be installed in the existing 128 water reservoirs in the country, covering 10% to 30% of the water surface, varies between 4.77 GW to 14.31 GW while the annual solar electricity generation varies between 6,435.2 GWh to 19,305.6 GWh.…”
Section: B Floating Photovoltaics and Climate Change In Greecementioning
confidence: 99%
See 3 more Smart Citations
“…They proposed the delay of the energy transition for some years for a better preparation of the national plan. Vourdoubas [31] has estimated the solar electricity generation from FPVs in water reservoirs in Greece. The author estimated that the nominal power of the FPVs that can be installed in the existing 128 water reservoirs in the country, covering 10% to 30% of the water surface, varies between 4.77 GW to 14.31 GW while the annual solar electricity generation varies between 6,435.2 GWh to 19,305.6 GWh.…”
Section: B Floating Photovoltaics and Climate Change In Greecementioning
confidence: 99%
“…It is predicted that the power of the hydro-pumpedstorage systems in Greece will be at 2.5 GW by 2030 compared to current absence of these energy storage systems. Vourdoubas [30] has investigated the possibility of using FPVs in the hybrid energy system in the island of El Hierro, Spain and in the planned hybrid energy system in the island of Crete, Greece. The author stated that the installation of FPVs on the water reservoirs of the hybrid energy plant in El Hierro, with coverage ratio 30%, increases its annual electricity generation by 6.06% while in the planed hybrid energy system in Crete by 33.78%.…”
Section: B Floating Photovoltaics and Climate Change In Greecementioning
confidence: 99%
See 2 more Smart Citations
“…They also mentioned that their estimations indicated that roughly around 15,000 M 3 to 25,000 M 3 of water can be saved annually for each MWp of FPVs installed in basins that is very important in arid regions while the annual energy yield can be increased by 10%. Reference [18] has estimated the potential for electricity generation from FPVs installed in the existing water reservoirs in the island of Crete, Greece. The author stated that the estimated nominal power of floating photovoltaics that can be installed in these water dams, with coverage ratio at 0.1 to 0.3, varies between 55.76 MWp to 167.3 MWp while the annual electricity generation from the floating photovoltaics varies between 78.3 GWh to 234.9 GWh.…”
Section: B Use Of Floating Photovoltaics In Several Countriesmentioning
confidence: 99%